Essentials of Law and Ethics for Pharmacy Technicians - Dung, Houchi (CRC Press pharmacy education series, 2012)
Addressing the latest procedural, ethical, and technological developments in this rapidly changing field, this third edition of a bestseller includes an appendix on the legal standing of electronic transmission of prescriptions. It covers U.S. state and federal regulations pertaining to the administration of new medications, including birth control and the morning-after pill, as well as current regulations on over-the-counter label claims. An essential resource for students as well as practicing technicians, this reference brings together the information that pharmacy technicians need to practice in a manner that is both legal and ethical.